Sosialisasi Batas Usia Nikah Berdasarkan Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan Sebagai Upaya Pencegahan Perkawinan Dini di Sekolah Menengah Atas Negeri 9 Jakarta - Purbowati, Lindri; Cendhayanie, Rara Amalia; Sulisrudatin, Nunuk; Aprilliani, Shilvyana; Purnamasari, Defi (Civiliza Publishing, 2024)
The determination of the age limit for marriage is stated in UU No.16 Tahun 2009 article (1), where marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years. However, data from the Central Statistics Agency (BPS) shows that 33.76% of young people in Indonesia recorded their first marriage age in the range of 19-21 years in 2022. As many as 19.24% of young people who first married when they were 16-18 years old. Early marriage has an impact on children, because there is no readiness both mentally and economically. Therefore, the Socialization of Law Number 16 of 2009 concerning the age of marriage as an effort to prevent early marriage was held at the State Senior High School 9 Jakarta which aims to provide legal awareness as well as enlightenment regarding the prevention of early marriage and provide education on mental readiness to become parents for children. The implementation of the socialization began with a pretest which was conducted orally to find out the initial understanding of the participants, then after that it began with material presentation and question and answer discussion for 2 hours. The results of this activity show that based on the participants' posttest results there is an increase in understanding about the age of marriage and the prevention of early marriage.